NAHDLATUL 'ULAMA'S PHILANTHROPY: THE AID FOR STRATEGY EDUCATION FINANCIAL - Aqimi Dinana; Ainur Rahman; Zainal Arifin (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2021)
The study aims the strategy for managing ZIS funds (Zakat, Infaq, and Sadaqah) for carried out to finance education in NU CARE-LAZISNU DIY. The research uses observation data collection methods, interviews, literature studies, and media internet information. In-depth interviews take for as primary data sources and online media as secondary data sources. The results show that NU CARE-LAZISNU DIY collects zakat, infaq, and sadaqah with various methods. The manual payment is the NU CARE-LAZISNU DIY office management. The internet system uses kitabisa.com portal. The aid method develops with the following increasingly cellular devices. The interface official NU CARE-LAZISNU DIY portal is the access to calculate zakat in philanthropy. The user of the NU CARE-LAZISNU DIY education is LP Ma'arif NU DIY as a fellow funding from PWNU DIY. However, NU CARE-LAZISNU DIY puts the engagement philanthropy for scholarships apply. The donator put the trust for management aid that is balanced for increasing statistic for aid fundraising zakat philanthropy scholarship education.